Relasi Antara Filantropi Melalui Crowdfunding dengan Nilai Selebritas - Alven, Alya Karamina; Sadasri, Lidwina Mutia (FISIP Universitas Atma Jaya Yogyakarta, 2019)
The activity of crowdfunding through the internet-based platform is becoming a usual thing in Indonesia. Some celebrities do this kind of activity in the context of birthday crowdfunding. The objective of this research is to analyze the relations between celebrity’s philantrophy through crowdfunding and its implication to the celebrity. This is a quantitative research with questionnaire as the data collection instrument to analyze the impact of crowdfunding to the value of Indonesian celebrity, Luna Maya. The findings of this research show the impact that arise from internet-based platform that enabling celebrity to build her visibilities on public’s opinion through crowdfunding.Keywords: celebrity, crowdfunding, philantrophy